Impact of DBP on all-cause and cardiovascular mortality: results from the National Health and Nutrition Examination survey, 1999–2014. Issue 1 (January 2022) - Bae, Eunjin; Rocco, Michael V.; Lee, Jeonghwan; Park, Jae Yoon; Kim, Yong Chul; Yoo, Kyung Don; Kim, Eun Young; Park, Dong Jun; Lim, Chun Soo; Kim, Yon Su; Lee, Jung Pyo
Abstract : Introduction: Hypertension is common and has a significant effect on cardiovascular morbidity and death. However, despite the development of several guidelines to manage SBP, there is little research or guidance on the evaluation and management of DBP or isolated diastolic hypertension (IDH). Method: To determine the association of DBP with all-cause and cardiovascular mortality, we used NHANES data from 1999 to 2014 and included adults aged at least 18 years. The relationship between DBP, IDH and all-cause, cardiovascular mortality was evaluated. Results: Of the 35 109 participants, all-cause death occurred in 10.6%, and cardiovascular death occurred in 2.1% over a median follow-up of 7.2 years. Multivariate Cox regression analysis revealed that the risk of all-cause mortality was significantly higher in the lowest (⩽56.9 mmHg) DBP groups than in the reference group (DBP 74–76.9 mmHg). However, the risk of cardiovascular mortality was significantly higher in the lowest and highest (≥83 mmHg) DBP group than in the reference group. The risk of all-cause mortality was higher for most groups with SBP at least 140 mmHg than for the reference group with DBP 74–76.9 mmHg and SBP 100–139.9 mmHg. Both the 2018 ESC/NICE and the 2017 AHA/ACC-defined IDH was not significantly associated with all-cause mortality. Conclusion: DBP and all-cause mortality had an inverse relationship, whereas DBP and cardiovascular mortality had a U-shaped relationship, with the DBP reference group having the lowest risk for all-cause and cardiovascular mortality. There was no significant relationship between IDH and death. Abstract : Supplemental Digital Content is available in the text